Knowledge, Attitude and Practice regarding dental pulp treatment in teaching sector of South Punjab - Mehwish Rafiq, Jaffar Hussain Bukhari, Malik Saleem Shaukat, Mehvish Saleem, Anam Tahir, Shamima Abdullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study had four-fold objective; to evaluate the dentists’ choice about removal of caries, to know the preferred material for direct and indirect pulp capping and to find out the influence of clinical experience, post-graduation and workplace on treatment modalities. Methodology: A cross-sectional study was performed on 460 dentists belonging to dental colleges of South Punjab. Non-probability convenience sampling was done. Information about work experience, post-graduation and workplace, caries removal, direct and indirect pulp capping material was collected. SPSS version 22 was used to analyze data. Frequencies, percentages and association of treatment options with other variables were found out. Results: Out of 429 participants, 50% selected to remove total caries and restore temporarily in first visit then permanent filling in second. Calcium hydroxide was the most preferred material (61%) for direct pulp capping, whereas for indirect, it was a combination of CH, GIC and adhesive, also opted by post-graduates significantly more than graduates (p=0.02). No association of work experience and post-graduation had no association with questions about treatment modalities (p = 0.19 and 0.16 respectively). In private sector, first treatment option and a combination of CH, GIC, adhesive and composite for indirect capping was opted significantly more than public sector (p=03 and p=02 respectively), whereas, for direct capping CH was opted significantly more in public than private (p=0.01). Conclusion: The preferred treatment was the complete caries removal and temporary filling in first visit followed by permanent filling in second. Calcium hydroxide was the material of choice for pulp capping, also significantly more in public sector than private. In deep cavities, the combination of CH and GIC was preferred for lining under composite resin. The work experience and post-graduation of dentists had no significant influence on treatment options or material used for pulp capping. Keywords: Biodentine, pulp capping, calcium hydroxide, mineral trioxide aggregate